2017
DOI: 10.1016/j.bej.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon dioxide availability on succinic acid production with biofilms of Actinobacillus succinogenes

Abstract: Succinic acid productivity starts to decrease with decreasing dissolved CO 2 below an upper threshold  The decrease in productivity occurs at a constant flux distribution up to a lower CO 2 threshold  Below the lower threshold, succinic acid yields decrease as flux shifts to C 3 pathways  Ethanol formation increases with decreasing dissolved CO 2 below the lower threshold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Actinobacillus succinogenes can metabolize a broad spectrum of carbon sources, including C5 and C6 sugars, disaccharides, and other carbon sources, such as mannitol, glycerol, cane molasses, whey, wheat, and corn-stover hydrolysates (Table 2). [35][36][37][38][39][40] Substrate cost generally accounts for around 50% in biotechnological processes. The adoption of low-cost substrates for succinic acid production is one of the critical parameters to make the bioprocess more economical.…”
Section: Wide Carbon Utilization Spectrum Of a Succinogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinobacillus succinogenes can metabolize a broad spectrum of carbon sources, including C5 and C6 sugars, disaccharides, and other carbon sources, such as mannitol, glycerol, cane molasses, whey, wheat, and corn-stover hydrolysates (Table 2). [35][36][37][38][39][40] Substrate cost generally accounts for around 50% in biotechnological processes. The adoption of low-cost substrates for succinic acid production is one of the critical parameters to make the bioprocess more economical.…”
Section: Wide Carbon Utilization Spectrum Of a Succinogenesmentioning
confidence: 99%
“…Metabolic pathway for succinic acid productionIn A. succinogenes, glucose is first metabolized to phosphoenolpyruvate (PEP) by the glycolysis or oxidative pentose phosphate pathway. Then, PEP is converted into pyruvate, formate, acetate, and ethanol via the C 3 pathway or into succinic acid via the C 4 pathway36 …”
mentioning
confidence: 99%
“…One such potential bioprocess is the production of succinic acid (SA) platform chemical using bioreactors of Actinobacillus succinogenes biofilms. The production of SA with A. succinogenes has been subjected to intense research scrutiny in the open literature, exploring steady-state metabolic flux distributions at various fermenter conditions [2][3][4][5], rate comparisons of biofilm and suspended modes [3,5], fermentations of various sugar types including hydrolysate streams [6][7][8], and using different reactor configurations [3,9,10]. Maharaj et al [5] observed that specific succinic acid (SA) productivity (per mass of biomass) decreased with increasing concentrations of SA, which was attributed to possible changes in the composition of the biofilm or fraction of the metabolically active cells within the biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…yields) between succinate, acetate and formate remained constant. Below 3.9 mM dissolved CO2 (or 17% saturation), the yield of succinate also decreased, as flux was diverted towards other products [113].…”
Section: Co2 Limitation In Succinic Acid Producersmentioning
confidence: 99%
“…By equalizing the energy charges of the different nucleotide pools, it will nullify any effects that a difference in energy charge would have, if indeed there is a difference. Worthwhile as well might be to accurately determine the concentration at which CO2 becomes limiting, as was done by Herselman et al (2017) [113], for a wide range of succinate producers that either rely on ATP, or GTP-dependent PEP carboxykinases, in order to see if there is a difference.…”
Section: Open Questions Regarding Pseudoclostridium Thermosuccinogenesmentioning
confidence: 99%